January Effect Phenomenon on Abnormal Return in Stock of SOE Bank Listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 Period - Hasnawaty Hasnawaty; Muhammad Aqsa; Muammar Khaddapi (Institute of Computer Science (IOCS), 2022)
This study aims to determine whether there are abnormal returns of state-owned banks listed on the Indonesia Stock Exchange (IDX) and whether there are differences in abnormal returns between January and months other than Janary for the 2018-2020 period. The test results using SPSS.25 indicate that there is an abnormal return of BUMN bank shares on the Indonesia Stock Exchange. This study uses secondary data in the form of stock price data obtained through the IDX official website. The analytical method used in this research is the One Sample T-Test. The results of data analysis show that the January effect has a significant effect on abnormal returns on shares of state-owned banks listed on the IDX where the return variable value in January is sig. (2-tailed) is 0.011 (0.011 < 0.05 ) and the return variable other than January is sig. (2-tailed) of 0.279 (0.279 > 0.05). The results based on testing using the Paired-Samples T Test method showed a significant difference to the abnormal returns of state-owned banks in January with months other than January in a certain period.